Toughened transparent ps composite material and preparation method thereof
Patent Information
- Application Number
- CN202310171153.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-02-27
AI Technical Summary
[0003]通过共混的方式提高透明PS的韧性,目前有少量报道,但效果并不理想,要么PS的透明度大大降低,要么PS的冲击性能以及其他的力学性能并不理想
[0041]1、本发明使用了一种新颖的复合的透明材料体系:1)利用材料的相容性很好但折射率不同,通过控制材料间的配比来调节材料的折射率;2)选择合适的增韧剂复配体系,通过增韧剂的配比来调节增韧体系的折射率,使得增韧体系的折射率与主体材料的折射相近,使得材料整体折射率一致,保持了复合材料的透明性,又提高了材料的韧性。
Smart Images

Figure BDA0004098610720000021 
Figure BDA0004098610720000041 
Figure BDA0004098610720000081
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, specifically relating to a toughened transparent PS composite material and its preparation method. Background Technology
[0002] Polystyrene (PS) has been widely used in many fields due to its high rigidity, good transparency, excellent water and chemical resistance, good electrical insulation and molding processability, and low cost. However, PS still has drawbacks such as low impact strength and high brittleness, which limit its application in some areas. Currently, PS is mainly modified through polymerization, grafting, and blending, such as MABS, MS, and MBS. Although these methods increase toughness and reduce brittleness, resulting in good effects, their production costs are high due to limitations in polymerization equipment and production scale, which hinders their widespread adoption. Aspartate resin (AS) and GPPS have excellent transparency and are inexpensive, but their low impact strength and high brittleness also limit their applications. For example, patent CN201610921324.8 discloses a flame-retardant PS composite material and its preparation method, which is made from the following components in parts by weight: 50-80 parts PS; 20-30 parts modified palygorskite; 20-30 parts flame retardant; 6-12 parts synergistic flame retardant; 0.1-0.5 parts antioxidant; and 0.1-0.3 parts lubricant. The natural palygorskite has a small specific surface area and is modified with HCl. + Replaced Mg + The Si-O-Mg-O-Si bonds are transformed into two Si-OH bonds, connecting the internal channels and increasing the specific surface area, allowing palygorskite to be better dispersed in the PS matrix. Simultaneously, octadecyltrimethylammonium bromide can react with the hydroxyl groups on the palygorskite, grafting organic matter onto the palygorskite surface, improving the compatibility between palygorskite and PS, and indirectly enhancing the physical properties of the PS composite material. Patent CN202211395101.4 discloses a PS composite material made from polystyrene and europium nitrate as raw materials, using N,N-dimethylformamide as a solvent, and constructed from polystyrene PS / europium ion composite nanofibers obtained through a sol-gel process and electrospinning technology. By modifying the PS plastic with europium ions, the PS composite material exhibits improved luminescence properties, ease of processing and molding, and corrosion resistance. Furthermore, the electrospinning of the nanofiber material further reduces the weight-to-volume ratio of the PS composite material, thereby achieving lightweighting.
[0003] While there are a few reports on improving the toughness of transparent PS through blending, the results are not ideal; either the transparency of PS is significantly reduced, or the impact resistance and other mechanical properties of PS are not satisfactory. Compatibility and refractive index are the two most important problems encountered in the preparation of high-toughness transparent PS, and there are currently no good solutions.
[0004] Therefore, further research into how to prepare economical, highly transparent, highly tough, and mechanically superior toughened transparent PS composites through blending processes can significantly reduce the cost of highly toughened transparent PS and expand the application range of PS. Summary of the Invention
[0005] Objective of the Invention: To overcome the shortcomings of existing technologies, this invention provides a toughened transparent PS composite material and its preparation method. This invention introduces AS, PMMA, SBS, and K-resin (styrene-butadiene copolymer) into the GPPS system to prepare an economical, highly transparent, highly tough, and mechanically superior toughened transparent PS composite material. This improves the flexibility of preparation, is not limited by polymerization capacity and production scale, significantly reduces the cost of highly toughened transparent PS, and expands the application range of PS.
[0006] Technical solution: To achieve the above-mentioned objectives, the technical solution of this invention is as follows:
[0007] On one hand, the present invention provides a toughened transparent PS composite material, wherein the PS composite material comprises raw materials in the following weight ratio:
[0008]
[0009] Specifically, the mass ratio of GPPS, AS and PMMA is 1:1:2.
[0010] Specifically, the refractive index of the GPPS is 1.59.
[0011] Specifically, the refractive index of the AS is 1.57.
[0012] Specifically, the refractive index of the PMMA is 1.49.
[0013] Specifically, the mass ratio of SBS to K adhesive is 1:3.
[0014] Specifically, the refractive index of the K-resin is 1.57.
[0015] Specifically, the average molecular weight of the SBS is 80,000 to 120,000.
[0016] Specifically, the organic-inorganic hybrid nanopowder has a size of 200-400 nm, and the nanopowder is hybrid silicon dioxide containing benzene rings.
[0017] Specifically, the raw material for preparing the organic-inorganic hybrid nanopowder is 1,4-bis(triethoxysilyl)benzene (BTEB).
[0018] More specifically, the preparation method of the organic-inorganic hybrid nanopowder is as follows: using chiral anionic surfactant C 11 H 23 CO-L-Leu-CO-NH-C 10 H 22 COO - Na + Using a gel as a template, it self-assembles into chiral nanofibers. Then, silicon sources APTMS and BTEB are added, and the mixture is polymerized through electrostatic adsorption sedimentation. After removing the template, the desired hybrid silica nanopowder is obtained.
[0019] More specifically, the preparation method of the organic-inorganic hybrid nanopowder is as follows: Weigh out chiral anionic surfactant C 11 H 23 CO-L-Leu-CO-NH-C 10 H 22 COO - Na + Place the mixture in a container, add deionized water and anhydrous ethanol as solvents, and under conditions of 0℃ and a shear force of Vox = 5, add APTMS first, then BTEB, stir and mix evenly. After the reaction is complete, let it stand overnight, and then heat it in an oil bath at 80℃ for 4 days. After the hydrothermal treatment is completed, remove the organic small molecule template with ethanol and concentrated hydrochloric acid. Repeat the operation 3 times, and then dry it to obtain organic-inorganic hybrid silica powder.
[0020] More specifically, the volume ratio of APTMS to BTEB is 1:3.
[0021] On the other hand, the present invention provides a method for preparing the above-mentioned toughened transparent PS composite material, the method comprising the following steps:
[0022] (1) Take GPPS, AS and PMMA, mix them evenly, and melt extrude to obtain composite material 1 with a refractive index of 1.53±0.01;
[0023] (2) Mix SBS and K glue evenly and melt extrude to obtain composite material 2 with a refractive index of 1.53±0.01;
[0024] (3) Mix composite material 1 and composite material 2 evenly, and add inorganic-inorganic hybrid nanopowder, thermo-oxidative aging antioxidant 1076, antioxidant 168 and photoaging aid UV-5411 into a high-speed mixer and dry mix for 3-5 minutes.
[0025] (4) The mixed raw materials are placed in a twin-screw extruder and granulated by melt extrusion. The process is as follows: Zone 1 180-190℃, Zone 2 190-200℃, Zone 3 200-210℃, Zone 4 200-210℃, Zone 5 210-220℃, Zone 6 220-230℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 220-230℃, Zone 10 210-230℃; the residence time is 1-2 minutes and the pressure is 12-18MPa.
[0026] Specifically, the PS composite material comprises the following raw materials in the indicated weight ratios:
[0027]
[0028] Specifically, the mass ratio of GPPS, AS and PMMA is 1:1:2.
[0029] Specifically, the refractive index of the GPPS is 1.59.
[0030] Specifically, the refractive index of the AS is 1.57.
[0031] Specifically, the refractive index of the PMMA is 1.49.
[0032] Specifically, the mass ratio of SBS to K adhesive is 1:3.
[0033] Specifically, the refractive index of the K-resin is 1.57.
[0034] Specifically, the average molecular weight of the SBS is 80,000 to 120,000.
[0035] Specifically, the organic-inorganic hybrid nanopowder has a size of 200-400 nm, and the nanopowder is hybrid silicon dioxide containing benzene rings.
[0036] Specifically, the raw material for preparing the organic-inorganic hybrid nanopowder is 1,4-bis(triethoxysilyl)benzene (BTEB).
[0037] More specifically, the preparation method of the organic-inorganic hybrid nanopowder is as follows: using chiral anionic surfactant C 11 H 23 CO-L-Leu-CO-NH-C 10 H 22 COO - Na+ Using a gel as a template, it self-assembles into chiral nanofibers. Then, silicon sources APTMS and BTEB are added, and the mixture is polymerized through electrostatic adsorption sedimentation. After removing the template, the desired hybrid silica nanopowder is obtained.
[0038] More specifically, the preparation method of the organic-inorganic hybrid nanopowder is as follows: Weigh out chiral anionic surfactant C 11 H 23 CO-L-Leu-CO-NH-C 10 H 22 COO - Na + Place the mixture in a container, add deionized water and anhydrous ethanol as solvents, and under conditions of 0℃ and a shear force of Vox = 5, add APTMS first, then BTEB, stir and mix evenly. After the reaction is complete, let it stand overnight, and then heat it in an oil bath at 80℃ for 4 days. After the hydrothermal treatment is completed, remove the organic small molecule template with ethanol and concentrated hydrochloric acid. Repeat the operation 3 times, and then dry it to obtain organic-inorganic hybrid silica powder.
[0039] More specifically, the volume ratio of APTMS to BTEB is 1:3.
[0040] Compared with the prior art, the positive and beneficial effects of the present invention are as follows:
[0041] 1. This invention uses a novel composite transparent material system: 1) Utilizing the good compatibility of materials but different refractive indices, the refractive index of the materials is adjusted by controlling the ratio between the materials; 2) Selecting a suitable toughening agent compound system, the refractive index of the toughening system is adjusted by the ratio of the toughening agents, so that the refractive index of the toughening system is similar to that of the main material, so that the overall refractive index of the material is consistent, maintaining the transparency of the composite material and improving the toughness of the material.
[0042] 2. This invention uses organic-inorganic hybrid nanomaterials with a size of less than 400 nm. On the one hand, this ensures the transmission of visible light, reduces light loss, and improves the transparency of the material. On the other hand, the organic-inorganic nanomaterials have good compatibility with the material, which greatly improves the mechanical properties of the material.
[0043] 3. This invention uses blending modification, which is not limited by polymerization equipment and production scale. The preparation process is simple, the cost is low, the design is highly flexible, and it is easy to promote.
[0044] 4. The transparent PS composite material obtained by this invention has a non-crosslinked structure and can be recycled and reused as a general PS material without causing secondary pollution. Detailed Implementation
[0045] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are not intended to limit the present invention, but only to illustrate the present invention. Unless otherwise specified, the experimental methods used in the following embodiments are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.
[0046] Experimental materials
[0047] The refractive index of GPPS is 1.59, and the dosage is 15-21%; the refractive index of AS is 1.57, and the dosage is 15-21%; the refractive index of PMMA is 1.49, the refractive index of K glue is 1.57, the average molecular weight of SBS is (8-12) ten thousand, the size of the organic-inorganic hybrid nanoparticles is 200-400 nm, the nanoparticles are hybrid silica containing benzene rings, and the raw material used to prepare the powder is 1,4-bis(triethoxysilyl)benzene (BTEB) containing benzene rings.
[0048] The preparation method of the organic-inorganic hybrid nanopowder is as follows: Weigh 20g of chiral anionic surfactant C 11 H 23 CO-L-Leu-CO-NH-C 10 H 22 COO - Na + The solution was placed in a container and 2.2 L of deionized water and 1.8 L of anhydrous ethanol were added as solvents. At 0°C and a shear force of Vox = 5, 10 mL of APTMS was added first, followed by 30 mL of 1,4-bis(triethoxysilyl)benzene (BTEB) at 5-second intervals. The mixture was stirred for 4 minutes. After the reaction was complete, the solution was left to stand overnight, then heated in an oil bath at 80°C for 4 days. After hydrothermal treatment, the organic small molecule template was removed using 4 L of ethanol and 1 L of concentrated hydrochloric acid. This process was repeated three times. The solution was then dried to obtain organic-inorganic hybrid silica powder.
[0049] Example 1
[0050] GPPS 21%, AS 21%, PMMA 42%, SBS 3%, K glue 9%, organic-inorganic hybrid silica powder 3%, UV-5411 0.4%, antioxidant 1076 0.4%, and antioxidant 168 0.2% are mixed evenly and melt-extruded through a twin-screw extruder to granulate. The process is as follows: Zone 1 180-190℃, Zone 2 190-200℃, Zone 3 200-210℃, Zone 4 200-210℃, Zone 5 210-220℃, Zone 6 220-230℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 220-230℃, Zone 10 210-230℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.
[0051] Example 2
[0052] Mix 20% GPPS, 20% AS, 40% PMMA, 4% SBS, 12% K-resin, 3% organic-inorganic hybrid silica powder, 0.3% UV-5411, 0.3% antioxidant 1076, and 0.4% antioxidant 168 evenly. Then, melt-extrude the mixture using a twin-screw extruder and granulate it. The process is as follows: Zone 1: 180-190℃, Zone 2: 190-200℃, Zone 3: 200-210℃, Zone 4: 200-210℃, Zone 5: 210-220℃, Zone 6: 220-230℃, Zone 7: 230-240℃, Zone 8: 230-240℃, Zone 9: 220-230℃, Zone 10: 210-230℃; Residence time: 1-2 minutes; Pressure: 12-18 MPa.
[0053] Example 3
[0054] Mix 18% GPPS, 18% AS, 36% PMMA, 6% SBS, 18% K-resin, 3% organic-inorganic hybrid silica powder, 0.5% UV-5411, 0.3% antioxidant 1076, and 0.2% antioxidant 168 evenly. Then, melt-extrude the mixture using a twin-screw extruder and granulate it. The process temperature is as follows: Zone 1: 180-190℃, Zone 2: 190-200℃, Zone 3: 200-210℃, Zone 4: 200-210℃, Zone 5: 210-220℃, Zone 6: 220-230℃, Zone 7: 230-240℃, Zone 8: 230-240℃, Zone 9: 220-230℃, Zone 10: 210-230℃; Residence time: 1-2 minutes; Pressure: 12-18 MPa.
[0055] Example 4
[0056] Mix 15% GPPS, 15% AS, 30% PMMA, 8% SBS, 24% K resin, 3% organic-inorganic hybrid silica powder, 0.3% UV-5411, 0.5% antioxidant 1076, and 0.2% antioxidant 168 evenly. Then, melt-extrude the mixture using a twin-screw extruder and granulate it. The process is as follows: Zone 1: 180-190℃, Zone 2: 190-200℃, Zone 3: 200-210℃, Zone 4: 200-210℃, Zone 5: 210-220℃, Zone 6: 220-230℃, Zone 7: 230-240℃, Zone 8: 230-240℃, Zone 9: 220-230℃, Zone 10: 210-230℃; Residence time: 1-2 minutes; Pressure: 12-18 MPa.
[0057] Comparative Example 1
[0058] GPPS 99%, UV-5411 0.5%, antioxidant 1076 0.3%, and antioxidant 168 0.2% are mixed evenly and then melt-extruded and granulated using a twin-screw extruder. The process is as follows: Zone 1 180-190℃, Zone 2 190-200℃, Zone 3 200-210℃, Zone 4 200-210℃, Zone 5 210-220℃, Zone 6 220-230℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 220-230℃, Zone 10 210-230℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.
[0059] Comparative Example 2
[0060] GPPS 72%, SBS 6%, K glue 18%, organic-inorganic hybrid silica powder 3%, UV-5411 0.5%, antioxidant 1076 0.3%, and antioxidant 168 0.2% are mixed evenly and then melt-extruded and granulated using a twin-screw extruder. The process is as follows: Zone 1 180-190℃, Zone 2 190-200℃, Zone 3 200-210℃, Zone 4 200-210℃, Zone 5 210-220℃, Zone 6 220-230℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 220-230℃, Zone 10 210-230℃; residence time is 1-2 minutes, and pressure is 12-18 MPa.
[0061] Comparative Example 3
[0062] Referring to Example 3, the size of the organic-inorganic hybrid silica powder was replaced from 200-400nm to 400-800nm, while the rest remained unchanged.
[0063] Comparative Example 4
[0064] Referring to Example 3, the ratios of GPPS:AS:PMMA = 1:1:2 and SBS:K adhesive = 1:3 were shuffled. Specifically, the following components were added: GPPS 18%, AS 21%, PMMA 42%, SBS 6%, K adhesive 9%, organic-inorganic hybrid silica powder 3%, UV-541 10.5%, and antioxidant 1076. 0.3% antioxidant and 1680.2% antioxidant are mixed evenly and melt-extruded through a twin-screw extruder, followed by granulation. The process temperature is as follows: Zone 1: 180-190℃, Zone 2: 190-200℃, Zone 3: 200-210℃, Zone 4: 200-210℃, Zone 5: 210-220℃, Zone 6: 220-230℃, Zone 7: 230-240℃, Zone 8: 230-240℃, Zone 9: 220-230℃, Zone 10: 210-230℃; Residence time is 1-2 minutes, and pressure is 12-18 MPa.
[0065] Experiment Example 1. Performance Evaluation
[0066] The granulated material prepared by the above method is dried in a forced-air oven at 60°C for 2-3 hours before being injection molded on an injection molding machine.
[0067] Tensile properties were tested according to ISO 527-2, with a specimen size of 150*10*4mm and a tensile speed of 50mm / min; bending properties were tested according to ISO 178, with a specimen size of 80*10*4mm, a bending speed of 2mm / min, and a span of 64mm; impact strength of simply supported beams was tested according to ISO 179, with a specimen size of 80*6*4mm and a notch depth of one-third of the specimen thickness.
[0068] The formula and performance test results are shown in Table 1 below:
[0069] Table 1: Formulation and Material Properties
[0070]
[0071] As can be seen from Examples 1-4 in Table 1, the material exhibits better transparency when GPPS:AS:PMMA = 1:1:2 and SBS:K glue = 1:3. This is because the refractive index of the composite material obtained by mixing GPPS, AS, and PMMA in a 1:1:2 ratio and then melt-extruding is 1.53 ± 0.01. Similarly, the refractive index of the composite material obtained by mixing SBS and K glue in a 1:3 ratio and then melt-extruding is also 1.53 ± 0.01. Utilizing the principle of "like dissolves like," and based on the good compatibility of the materials, adjusting the refractive indices to relatively close values results in good transparency. Furthermore, the data shows that the impact performance of the material increases with the increase of the toughening agent ratio. When the toughening agent (SBS + K glue) reaches 24%, the overall mechanical properties of the material reach their optimal levels, including the best impact performance and light transmittance. Comparative Example 1 and Example 3 demonstrate that the formulation system composed of GPPS, AS, PMMA, SBS, and K glue not only significantly improves the toughness of the material but also enhances its tensile, flexural, and other mechanical properties. Comparative Examples 2 and 3 show that while the addition of less AS and PMMA improves the impact, the light transmittance is low. This is because the refractive indices of the materials are inconsistent and not properly balanced, resulting in poor transparency. Comparative Examples 3 and 3 show that powder size affects material transparency. When the material size is larger than the wavelength of visible light, some light is blocked or reflected, affecting the light transmittance. Comparative Examples 4 and 3 show that good light transmittance cannot be achieved with arbitrary proportions of GPPS, AS, PMMA, SBS, and K-resin. Only under specific proportions can the refractive indices within the material be similar, resulting in good light transmittance. In conclusion, by selecting compatible transparent materials, adjusting the refractive indices to make them similar, and adding nanoparticles smaller than the wavelength of visible light, a high-performance, cost-effective, and tough transparent PS can be prepared.
[0072] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A toughened transparent PS composite material, characterized in that: The PS composite material comprises the following raw materials in the indicated weight ratios: The mass ratio of GPPS, AS and PMMA is 1:1:2; The refractive index of the GPPS is 1.59; the refractive index of the AS is 1.57; and the refractive index of the PMMA is 1.
49. The mass ratio of SBS to K adhesive is 1:3; The organic-inorganic hybrid nanoparticles have a size of 200-400 nm, and the nanoparticles are hybrid silicon dioxide containing benzene rings.
2. The PS composite material according to claim 1, characterized in that: The K-resin has a refractive index of 1.57; the SBS has an average molecular weight of 80,000-120,000.
3. The PS composite material according to claim 2, characterized in that: The raw material for preparing the organic-inorganic hybrid nanopowder is 1,4-bis(triethoxysilyl)benzene.
4. The PS composite material according to claim 3, characterized in that: The preparation method of the organic-inorganic hybrid nanopowder is as follows: using chiral anionic surfactant C 11 H 23 CO-L-Leu-CO-NH-C 10 H 22 COO - Na + Using a gel as a template, it self-assembles into chiral nanofibers. Then, silicon sources APTMS and BTEB are added, and the mixture is polymerized through electrostatic adsorption sedimentation. After removing the template, the desired hybrid silica nanopowder is obtained.
5. The PS composite material according to claim 4, characterized in that: The volume ratio of APTMS to BTEB is 1:
3.
6. A method for preparing the toughened transparent PS composite material according to any one of claims 1-5, characterized in that: The preparation method includes the following steps: (1) Take GPPS, AS and PMMA, mix them evenly, and melt extrude to obtain composite material 1 with a refractive index of 1.53±0.01; (2) Mix SBS and K glue evenly and melt extrude to obtain composite material 2 with a refractive index of 1.53±0.01; (3) Mix composite material 1 and composite material 2 evenly, and add inorganic-inorganic hybrid nanopowder, thermo-oxidative aging antioxidant 1076, antioxidant 168 and photoaging aid UV-5411 into a high-speed mixer and dry mix for 3-5 minutes. (4) The mixed raw materials are placed in a twin-screw extruder and granulated by melt extrusion. The process is as follows: Zone 1 180-190℃, Zone 2 190-200℃, Zone 3 200-210℃, Zone 4 200-210℃, Zone 5 210-220℃, Zone 6 220-230℃, Zone 7 230-240℃, Zone 8 230-240℃, Zone 9 220-230℃, Zone 10 210-230℃; the residence time is 1-2 minutes and the pressure is 12-18MPa.
Citation Information
Patent Citations
Flame retardant PS composite and method of processing flame retardant PS composite
CN106479071A
PS composite material and preparation method thereof
CN115652462A
High-impact-resistance transparent GPPS modification method
CN111875746A
GPPS transparent toughening modified material and preparation method thereof
CN113817275A
